Dentistry for babies: A preventive protocol - Cunha, Robson Frederico [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Percinoto, Célio [UNESP]; Saito, Tathiana Eiko [UNESP] (My University, 2000)
The objectives of this program were to educate the parents in the importance of preventive care and to establish protocols for oral health treatment and maintenance that reflected the oral disease risk of the infant. Since its inception, more than 1,000 infants have been enrolled in the program and compliance has been excellent.
Keywords: Infants; Preventive dental care